Balancing Hydrological Sustainability and Heritage Conservation: A Decadal Analysis of Water-Yield Dynamics in the Honghe Hani Rice Terraces - Linlin Huang; Yunting Lyu; Linxuan Miao; Sen Li (Hydrology)
The Honghe Hani Rice Terraces, a UNESCO World Heritage agroecosystem, embody a millennia-old synergy of cultural heritage and ecological resilience, yet face declining water yields amid land-use intensification and climate variability. This study employs the InVEST model and geographic detector analysis to quantify water-yield dynamics from 2010 to 2020 and identify their spatial and mechanistic drivers. Annual water yield averaged 558 mm, with cultivated lands contributing 33% of total volume, while built-up areas reached 980 mm per unit in 2018. A 31% decline by 2020, driven by cropland fragmentation and tourism growth, revealed persistent-yield hotspots in forested central-eastern terraces and cold spots in southwestern dryland margins. Land-use pattern accounted for 80–95% of yield variability, exacerbated by temperature interactions. Forests, delivering 68.7 million m3 over the decade, highlight the hydrological significance of traditional landscape mosaics. These findings advocate reforestation in critical recharge zones, terrace restoration to preserve agroecological integrity, and regulated tourism integrating rainwater harvesting to sustain water security and cultural heritage. By blending hydrological modeling with socio-cultural insights, this study provides a scalable framework for safeguarding terraced agroecosystems worldwide, aligning heritage conservation with sustainable development.